The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1136/neurintsurg-2014-011143.rep
|View full text |Cite
|
Sign up to set email alerts
|

Carotid stent infection: a rare but potentially fatal complication of carotid artery stenting

Abstract: SUMMARYInfections involving endovascular devices are rare and, to our knowledge, only three cases of infection with an inserted carotid stent have ever been reported. A 68-year-old man underwent carotid artery stenting (CAS) of the left proximal internal carotid artery. Two days after CAS the patient developed a high fever and investigation showed that the inserted carotid stent was infected. The infection could not be controlled despite adequate antibiotic therapy. Eventually a rupture of the carotid artery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…However, anticoagulant therapy could not be introduced in our case due to bleeding diathesis; therefore, aspirin alone was used as antiplatelet therapy. Although stent thrombosis occurred in our case, it was considered that sepsis was caused by E. coli , and it has been reported that stent infection is a potentially fatal complication [8] .…”
Section: Discussionmentioning
confidence: 67%
“…However, anticoagulant therapy could not be introduced in our case due to bleeding diathesis; therefore, aspirin alone was used as antiplatelet therapy. Although stent thrombosis occurred in our case, it was considered that sepsis was caused by E. coli , and it has been reported that stent infection is a potentially fatal complication [8] .…”
Section: Discussionmentioning
confidence: 67%
“…Contralateral cerebral embolism occurred after CAS for extracranial carotid stenosis [9]. Infection of the inserted carotid stent caused rupture of the carotid artery [10]. Cerebral vasospasm was noted after CAS [3].…”
Section: Discussionmentioning
confidence: 99%
“…Carotid stent infections are rare, with only four cases reported in the literature, 13 but they are a serious complication when they do occur. Once infected, stents act as a medium for bacteria to attach to the arterial wall, causing arterial wall destruction, thrombosis formation and eventual wall thinning and pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 99%